Urbanization dynamics and territorial management strategies: the case of Chapéu do Sol in Várzea Grande, Brazil - Gisele Carignani; Caio César Tomaz de Oliveira (ARQUISUR Revista)
The present study addresses the dynamics of urbanization and territorial management strategies in Várzea Grande, in the Metropolitan Region of the Cuiabá River Valley (RMVRC, by its initials in Portuguese), Brazil. The research critically analyzes the production and organization of the urban space, particularly in areas of unstructured expansion in contrast with urban voids in consolidated regions of the city. The goal is to identify both the factors contributing to the current urban configuration and the challenges in managing urban growth. The methodology combines literature review and document analysis. The review involved literature on urbanization, urban planning, and municipal legislation as well as historical processes in Várzea Grande. A records analysis was carried out to examine municipal laws, including the Master Plan, the Urban Land Division Law, and the Zoning Law. Geoprocessing tools and geographic information systems (GIS) mapped the spatial distribution of infrastructure, land use, and urban growth patterns. The results indicate that urban expansion in Várzea Grande is often directed towards areas lacking infrastructure, while large urban voids remain in consolidated areas. This dynamic leads to significant challenges for sustainable and effective urban planning, requiring integrated approaches that consider the existing infrastructure and promote the rational occupation of urban spaces.